Effect of Corporate Social Responsibility on Profitability of Polaris Bank Ltd, Bauchi - Hammayo, Abdulkadir Ahmed; Badara, Haruna Aliyu; Abdullahi, Safiya (Kashere Journal of Management Sciences, 2024)
This study is on the effect of corporate social responsibility on profitability of Polaris Bank Ltd, Bauchi. Primary source of data collection was used in this study, through questionnaire administration. The collected data were analyzed and hypothesis tested by the use of correlation and regression analyses. The result of the hypothesis showed that corporate social responsibility (measured by Contribution to community standard, good public image and better business environment) has significant positive effect on the profitability of Polaris bank ltd, Bauchi. The study revealed that Polaris Bank has incorporated social responsibility in terms of better business environment, contribution to the community standard of living hence good public image. The study recommends increase in allocation for corporate social responsibility and human resources development as a way of enhancing Polaris Bank ltd profitability